1994
DOI: 10.1055/s-0038-1642510
|View full text |Cite
|
Sign up to set email alerts
|

Haemostatic Activation before and after Surgery in Patients with and without Gastric Malignancy

Abstract: SummaryPre- and postoperative plasma levels of Prothrombin Fragment 1 + 2 (F1+2), Thrombin-antithrombin III complex (TAT), Fibrinopeptide A (FpA), Fibrin and Fibrinogen Degradation Products (FbDP, FgDP) and Soluble Fibrin (SF) were measured in 40 patients undergoing gastric surgery in order to compare patients operated for benign (n = 21) and malignant (n = 19) disease. Plasma levels of F1+2, TAT, FbDP and SF on the first postoperative day were significantly higher than before operation. F1+2 and FbDP levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…A significant increase of all clotting markers during the postoperative period compared with preoperative levels was observed, showing a similar degree of clotting activation in both groups of patients. Our results confirm that a significant activation of the coagulation system takes place after surgery [27]. It has also been suggested that the increase in these clotting markers may be predictive for the development of postoperative thrombosis, thus being useful in the detection of a prethrombotic state after surgery [281.…”
Section: Discussionsupporting
confidence: 76%
“…A significant increase of all clotting markers during the postoperative period compared with preoperative levels was observed, showing a similar degree of clotting activation in both groups of patients. Our results confirm that a significant activation of the coagulation system takes place after surgery [27]. It has also been suggested that the increase in these clotting markers may be predictive for the development of postoperative thrombosis, thus being useful in the detection of a prethrombotic state after surgery [281.…”
Section: Discussionsupporting
confidence: 76%
“…Serum peptidome analyses by either matrix‐assisted laser‐desorption ionization or surface‐enhanced laser‐desorption ionization time‐of‐flight mass spectrometry revealed FpA peptide as a m/z peak at around 1469 Da particularly upregulated in metastatic GC or in GC with lymph node metastasis, as well as in patients at high risk for GC . Previous laboratory assays showed that FpA levels increased with the extent of primary tumor in postoperative patients with malignant disease since its early stages …”
Section: Coagulation‐related Proteins and Cancermentioning
confidence: 99%
“…The decrease in inhibitor levels during the postoperative period would seem compatible with the well-known simultaneous increase in markers of hemostatic activation (whether due to consumption or lack of inhibition). We have previously reported levels of such mark ers in the same patients [5]. The cancer pa tients had higher levels of fibrinopeptide A and fibrin degradation products on day 0 and day 7, whereas levels of prothrombin frag ment 1+2, thrombin-AT complex and soluble fibrin did not differ on any of the days.…”
Section: Discussionmentioning
confidence: 88%
“…Two age-matched subgroups of a previously de scribed patient group were investigated [5]. In brief, 4 1 patients undergoing elective gastric surgery for either benign or malignant disorders were included after written informed consent.…”
Section: Patientsmentioning
confidence: 99%